Toward greater impact: A CGIAR Engagement Framework for Partnerships and Advocacy - CGIAR System Organization (2024)
CGIAR's Engagement Framework for Partnerships and Advocacy builds on the recommendations of the CGIAR System Council that for greater impact towards the transformation of food, land, and water systems in a climate crisis, a consistent approach to partnerships and advocacy is required. While CGIAR has always relied on engagement with an extensive and diverse network of partners around the world to deliver solutions that benefit millions of people, the One CGIAR reform has highlighted the need for collaboration to become more systemic to better capture strategic opportunities and synergies across the organization.